2022
DOI: 10.1136/bmjopen-2022-065250
|View full text |Cite
|
Sign up to set email alerts
|

Rate of glycaemic control and associated factors in patients with type 2 diabetes mellitus treated with insulin-based therapy at selected hospitals in Northwest Ethiopia: a multicentre cross-sectional study

Abstract: ObjectivesThis study was aimed to determine the level of glycaemic control and associated factors in patients with type 2 diabetes mellitus (T2DM) treated with insulin-based therapy.DesignsInstitutional-based multicentre cross-sectional study design was employed to conduct this study.SettingsThe diabetes follow-up clinics of selected hospitals in Northwest Ethiopia.ParticipantsAdult patients with T2DM treated with insulin-based therapy at the selected hospitals who met the eligibility criteria were the study p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
(54 reference statements)
1
5
0
Order By: Relevance
“…This is consistent with the previous studies [17][18][19]. In line with the previous studies [8,15,27,33], there was also a significant difference in the incidence of hypoglycemic episodes including rate of sever hypoglycemia between NPH and premixed insulin regimens, which hypoglycemic episodes were more likely to occur in patients treated with premixed insulinbased regimens compared with patients treated with NPH insulin regimens. The finding might be justified that the regular insulin component of the premixed insulin is more likely to be responsible for hypoglycemic episodes because of its short acting effects.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the previous studies [17][18][19]. In line with the previous studies [8,15,27,33], there was also a significant difference in the incidence of hypoglycemic episodes including rate of sever hypoglycemia between NPH and premixed insulin regimens, which hypoglycemic episodes were more likely to occur in patients treated with premixed insulinbased regimens compared with patients treated with NPH insulin regimens. The finding might be justified that the regular insulin component of the premixed insulin is more likely to be responsible for hypoglycemic episodes because of its short acting effects.…”
Section: Discussionsupporting
confidence: 92%
“…The magnitude of pooled poor glycemic control is lower than the findings of individual studies conducted in Saudi Arabia (74.6%, 74.9%), 90 , 91 Kenya (65.1%), 92 Bangladesh (82%), 93 India (78.2%), 15 Morocco 66.3%, 94 and Dares Salaam (69.7%) 95 as well as a recent finding in Ethiopia where 72.5% patients with T2DM have poor glycemic control. 96 However, it is lower than the findings in China and Zimbabwe, where 57.3% 97 and 58.2% 98 of diabetic patients had poor glycemic control, respectively. The differences in the sample size, study population, and reference points indicating glycemic control may be associated with differences in the elucidation of these discrepancies.…”
Section: Discussionmentioning
confidence: 68%
“…These findings indicate that patients who practice SMBG can obtain direct feedback regarding their blood glucose and may use that information to adjust their management and lifestyle modifications. The earlier findings also showed that practicing SMBG results in good glycaemic control,33 50 which in turn can help patients maintain their HRQoL. As a result, because SMBG is an important tool for improving patient self-management and clinicians may use it to guide management interventions, patients may be encouraged to use it, share their testing results with physicians and the clinicians may then act to make management decisions 51 52.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, obesity causes increased levels of fatty acids and inflammation, leading to insulin resistance, which in turn can result in poor glycaemic control and compromised HRQoL in patients. The earlier study also disclosed that patients with obesity were found to have poor glycaemic control, 33 which in turn could result in poor HRQoL. Health weight can prevent the progression of diabetes by improving blood glucose, blood pressure and lipid profiles that reduce the risk of complications, which in turn can maintain the HRQoL of patients at the optimum level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation